THE OXIDATION OF FISH OIL DURING EXTRACTION PROCESS AND STORAGE - Nhat, Dang Minh; Hang, Le Minh (Vietnam Journal of Science and Technology, 2012)
Fish oil has high nutritional value, but easily undergoes oxidation to form many undesirable products. The aim of our study was to evaluate the effect of fish oil extraction methods on the extraction yield and the oxidation state of the product. Besides, the effect of natural and synthetic antioxidants on the quality of fish oil during extraction and storage ere also examined. Extraction methods selected in this  study included: NMKL-No.131 method, Soxhlet method and mechanical methods with and without addition of ginger and tea extract. The oxidation of extracted fish oil was evaluated by peroxide value (PV). The results have shown that the method NMKL-No.131 had provided highest extraction yield, but the oil had been the most oxidized. Meanwhile, the mechanical method provided lower extraction yield, but the quality of the product was much more better, met the requirements of commercial fish oil product. The addition of ginger and tea extract to fish suspension before extraction lowered the peroxide value of extracted fish oil significantly.The presence of ginger and tea extract in fish oil also retarded the oxidation, this effect was ashigh as the effect of the popular synthetic antioxidant BHT.